Membangun Integritas Diri dan Berkarakter Baik Sebagai Bekal Menuju Generasi Unggul - Maria, Elvie; Manalu, Brilliant Handyman; Victor, Victor; Sudarso, Andriasan; Nadapdap, Kristanty M. N.; Simanjuntak, Arthur (Universitas Methodist Indonesia, 2024)
Someone is said to be superior when they have something that other people don't have, do something better than other people, or are able to do something that other people can't do and achieve something that other people can't achieve, and in this era full of competition like today, people use various ways to outperform others. Being superior it's prestigious, but having superiority achieved by violating morals and noble values is certainly not a commendable thing. In the midst of the moral crisis occurring in the general public, especially generation Z, such as; bullying, violence among teenagers, blurring of good and bad morals, dishonesty become commonplace, fanatical attitudes towards certain groups, low respect for parents and teachers, high levels of self-destructive behavior such as use of drugs, alcohol, gambling and free sex, bad language easily blurted out; cursing, scolding, ridicule, blasphemy, slander, swearing, without paying attention to other people's feelings, mutual suspicion, low level of concern, it is easy for hatred to arise between people. St. Yoseph High School Medan, one of the best schools in the city of Medan, is very sensitive to what is happening in society today, but is optimistic that it is not too late to improve it. Located in the St Yoseph Medan High School Hall, holding training in the form of seminars for Class XII students, aimed at broadening their knowledge about the importance of having personal integrity and good character that will lead them to become a superior generation, and not taking actions that can harm themselves, their families, the surrounding community, as well as the nation and state.